Carbon-based 2D-layered Rb0.15Cs2.85Sb2ClxI9−x solar cells with superior open-voltage up to 0.88 V. (October 2021) - Guo, Yixin; Zhou, Jun; Zhao, Fei; Wu, Yuyao; Tao, Jiahua; Zuo, Shaohua; Jiang, Jinchun; Hu, Zhigao; Chu, Junhao
Abstract: Although the emerged hybrid lead (Pb) halied perovskite solar cells (PSCs) have rapidly held the center stage of photovoltaic field in recent years, the instability of organic cation and toxicity of Pb still remain big obstructions for their further commercial application. Antimony (Sb)-based Cs3 Sb2 Clx I9−x perovskite-like compound has been considered as a promising candidate to simultaneously resolve the toxicity and thermal instability issues of hybrid Pb-based PSC. However, the power conversion efficiency (PCE) of Cs3 Sb2 Clx I9−x perovskite-like solar cell (PLSC) is still very low due to the poorer film qualify and higher defects density compared with Pb-based perovskites. What is worse, the open voltage of currently state-of-the-art Sb-based PLSC is below 0.73 V which is far away from the requirement for high efficient solar cells. Herein, we manipulate the crystal structure and improve the film quality of Cs3 Sb2 Clx I9−x by partially exchanging the A-site inorganic cation with rubidium (Rb) or potassium (K). A less-pinhole perovskite-like film with suppressed 0D phase and reduced defects can be achieved by precisely controlling the doping concentration. Low-cost planar Sb-based inorganic PLSCs were assembled with carbon electrode for the first time and the interface energy level was properly aligned by using Nb2 O5 electron transport layer (ETL) instead of conventional TiO2 ETL. A PCE of 2.46% can be achieved with a respectable open voltage (Voc ) of 0.88 V, which is the highest PCE reported for Sb-based inorganic PLSCs to the best of our knowledge. This work will boost the further development of wide-bandgap Pb-free inorganic perovskite-like compounds for realizing broad applications in outdoor/indoor photovoltaic devices, tandem solar cells and photodetectors. Graphical Abstract: ga1 Highlights: Improved film quality and suppressed zero-dimension orientation by cation substitution. Low-cost and efficient carbon based perovskite-like solar cell. Interface engineering to reach a unprecedented open voltage of 0.88 V. A record PCE of 2.46% for inorganic Sb-based perovskite-like solar cells.